Students with Disabilities and eLearning in Australia: Experiences of Accessibility and Disclosure at Curtin University - Kent, Michael; Ellis, Katie; Giles, M. (2018)
This article reports on a study into students with disabilities and their experiences of eLearning at Curtin University in Australia. The results are compared to an earlier study of students at Open Universities Australia (OUA) (Kent 2016). The results confirm the earlier study’s findings that these students are drawn to eLearning. The prevalence of mental illness and medical disabilities as the two most frequent impairment types amongst students with disabilities in Australia was confirmed, along with a need to rethink universal design for eLearning to better accommodate these students. It also finds that the students had difficulty accessing online platforms and notably those provided directly by the university. This survey confirmed that students at Curtin University were more aware than their OUA counterparts of accommodations that could be made to help with their studies. It also showed that, when used, those accommodations were more successful. However, the study also reported that Curtin University students were more likely to not disclose their disability as part of their studies.